When Life and Heart Collide: A Series of 50 Peripartum Cardiomyopathy Cases - Santiago Roibal , Rosali; Carbonell González, Marlon; Cabrera Rodríguez, Deborah (Salud Integral y Comunitaria, 2026)
Introduction: Peripartum cardiomyopathy (PPCM) is a rare but serious form of heart failure occurring in late pregnancy or early postpartum. Data on Cuban women remain scarce. Objective: To describe the clinical characteristics, management, and six-month outcomes of Cuban women with PPCM and identify predictors of poor recovery. Methods: This prospective observational study included 50 consecutive women diagnosed with PPCM at Hospital ClínicoQuirúrgico Miguel Enríquez, Havana, Cuba (January 2022–December 2024). Demographic, obstetric, clinical, laboratory, and echocardiographic data were collected, including left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS). Treatment, intensive care use, and follow-up at 1, 3, and 6 months were recorded. Recovery was classified as complete (LVEF ≥50%) or partial (LVEF 35–49%). Logistic regression identified predictors of poorrecovery. Results: The mean age was 29 ± 6 years; 70% were diagnosed postpartum. Common comorbidities included preeclampsia (18%),gestational diabetes (10%), and hypertension (12%). Dyspnea (84%), edema (62%), and fatigue (56%) predominated. The mean baseline LVEF was 33 ± 7%. ICU admission was required in 28%, inotropic support in 10%, and mechanical circulatory support in 2%. At six months, 42% achieved complete recovery, 26% partial, and 32% had persistent dysfunction. Predictors of poor recovery were baseline LVEF <30% (OR 4.2), preeclampsia (OR 3.1), and diagnosis more than two weeks postpartum (OR 3.7). Mortality was 4%. Conclusions: PPCM in this Cuban cohort was predominantly postpartum and showed high recovery rates with early diagnosis and therapy. Low LVEF, preeclampsia, and diagnostic delay predicted adverse outcomes.